Susceptibilidad antibiótica de estafilococos aislados de muestras de leche provenientes de mastitis bovina - Srednik, M.E. (2016)
Mastitis is a disease that affects the health of cattle and causes great economic losses. The most prevalent microorganisms in Argentina belong to the genus Staphylococcus, being the main pathogen S. aureus, though coagulase-negative Staphylococci (CNS) have gained importance for the ability to express virulence factors and antimicrobial resistance. The aim of this study was to determine phenotypically in vitro minimum inhibitory concentrations of betalactams and macrolide-lincosamide against staphylococci isolated from mastitic milk. We studied (n=162) isolates, (n=65) S. aureus and (n=97) CNS. The 33,8% (22/65) of S. aureus presented resistance\nto penicillin, being the MIC90: 0,5 µg/ml, the 7,7% (5/65) to erythromycin with a MIC90: 1 µg/ml and 6,1% (4/65) to clindamycin with a MIC90: 0,1 µg/ml. The 30,9% (30/97) of CNS were resistant to penicillin being the MIC90: 0,25 µg/ml, the 7,2% (7/97) to erythromycin with a MIC90: 0,5 µg/ml, the 4,2% (4/97) to clindamycin with a MIC90: 0,12 µg/ml and 3,1% (3/97) to oxacillin being the MIC90: 0,38 µg/ml. Methicillin-resistance was not observed in S aureus. Bacteriological diagnosis and susceptibility determination with proper management of dairy herd are essential for disease control.